Advances in Information and Intelligent Systems - Ras, Zbigniew W.; Ribarsky, William; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This volume gives an overview of research done by CCI faculty in the area of Information & Intelligent Systems. Presented papers focus on recent advances in four major directions: Complex Systems, Knowledge Management, Knowledge Discovery, and Visualization. A major reason for producing this book was to demonstrate a new, important thrust in academic research where college-wide interdisciplinary efforts are brought to bear on large, general, and important problems. As shown in the research described here, these efforts need not be formally organized joint undertakings (through parts could be) but are rather a convergence of interests around grand themes. Taken together, the sections and chapters in this book reveal a variety of methods and tools that can be applied to quite diverse types of data and analysis problems but where each produces knowledge and features that can be combined, organized, explored, understood, and used in common ways (for example, through interactive visualization interfaces).
Complex Systems -- Complex Adaptive Systems: How Informed Patient Choice Influences the Distribution of Complex Surgical Procedures -- Making Sense of Complex Systems through Integrated Modeling and Simulation -- Towards a General Tool for Studying Threshold Effects Across Diverse Domains -- Knowledge Discovery -- Modeling and Extracting Deep-Web Query Interfaces -- On the Quantification of Identity and Link Disclosures in Randomizing Social Networks -- Polyphonic Music Information Retrieval Based on Multi-label Cascade Classification System -- Accurate and Robust Centerline Extraction from Tubular Structures in Medical Images -- Knowledge Management -- Incorporate Visual Analytics to Design a Human-Centered Computing Framework for Personalized Classifier Training and Image Retrieval -- A Multi-strategy Approach to Geo-Entity Recognition -- Monte-Carlo Tree Search and Computer Go -- Ontology Guided Risk Analysis: From Informal Specifications to Formal Metrics -- Decentralized Peer-to-Peer Botnet Architectures -- Visualization -- A Dimension Management Framework for High Dimensional Visualization -- Year-Long Time-Varying 3D Air Quality Data Visualization -- Embedding Information Visualization within Visual Representation -- Interaction Volume Management in a Multi-scale Virtual Environment.
Keywords: Computer science; Data mining; Artificial intelligence; Image processing; Applied mathematics; Engineering mathematics; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Image Processing and Computer Vision; Appl.Mathematics/Computational Methods of Engineering; Electronic books